2015
DOI: 10.1177/1757177415588380
|View full text |Cite
|
Sign up to set email alerts
|

Using surveillance data to reduce healthcare–associated infection: a qualitative study in Sweden

Abstract: Introduction: Healthcare-associated infection (HAI) surveillance data can be used to estimate the scope, spread and location of infections, monitor trends, evaluate preventive efforts, and improve practices, policy and facility planning. In Sweden, national point prevalence surveys (PPS) have been conducted twice yearly in all county councils since 2008. Aim:The aim of this study was to identify key obstacles concerning the HAI surveillance process.Methods: Twenty-two infection control practitioners (ICPs) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Similar roles are described in numerous frameworks and models applied in implementation science (Nilsen, 2015). Although having champions of EBP has been shown to be important for successful implementation of EBP in various settings (Aarons, Sommerfeld, & Willging, 2011;Berta et al, 2005;Greenhalgh et al, 2004;Simpson, 2002), there are also disadvantages in becoming too dependent on individuals because sustainability of EBP may be compromised if these individuals retire or take up other job opportunities (Damschroder et al, 2009;Ridelberg & Nilsen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar roles are described in numerous frameworks and models applied in implementation science (Nilsen, 2015). Although having champions of EBP has been shown to be important for successful implementation of EBP in various settings (Aarons, Sommerfeld, & Willging, 2011;Berta et al, 2005;Greenhalgh et al, 2004;Simpson, 2002), there are also disadvantages in becoming too dependent on individuals because sustainability of EBP may be compromised if these individuals retire or take up other job opportunities (Damschroder et al, 2009;Ridelberg & Nilsen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This tension may explain, in part, the difficulties in encouraging transparency around SSI diagnosis and surveillance as surgeons cannot reconcile the accountability for high rates, which they accept to be theirs, with their belief that SSI prevention is neither completely their responsibility, nor always completely possible. An appropriate sharing of surveillance data may help foster a sense of team accountability by reflecting the complex responsibility in SSI prevention [16]. The strategy of output dissemination should meet the stakeholder needs, be timely, high quality, with accessible content and delivering interpretation and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, previous studies into SSI prevention have largely used quantitative methods to assess the impact of or compliance with strategies. Few studies have explored the factors that influence surgical staff behaviours and IC practices [16, 17]. Qualitative research is now needed to explore the drivers of compliant and non-compliant IC behaviour in surgery and the impact of social and organisational context on practices.…”
Section: Introductionmentioning
confidence: 99%
“…169 Surveillance data regarding HCAIs can be used to assess the extent, escalation, and status of infections, to examine, scan and monitor trends of infection rates, inform alert programs, and improve performances, strategy and competence development. 170 , 171 One Scottish study suggested that because the surveillance system in Scotland was not so well-organized, the time taken to first recognize HCAIs was longer than the gold standard. 172 This study also found that the time at which HCAIs are recognized can be reduced either by “increasing the number of hospitals participating in surveillance or by optimally selecting which hospitals to include in a surveillance system.” 172 Two other Scottish studies echoed this, reporting that a better surveillance system could have prevented a considerable number of Staphylococcus aureus bacteremia (SAB) episodes.…”
Section: Methodsmentioning
confidence: 99%